2014
DOI: 10.1002/em.21927
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet A radiation potentiates the cytotoxic and genotoxic effects of 7H‐dibenzo[c,g]carbazole and its methyl derivatives

Abstract: 7H-Dibenzo[c,g]carbazole (DBC) is a heterocyclic aromatic hydrocarbon that is carcinogenic in many species and tissues. DBC is a common environmental pollutant, and is therefore constantly exposed to sunlight. However, there are limited data exploring the toxicity of DBC photoexcitation products. Here, we investigated the impact of ultraviolet (UV) A radiation on the biological activity of DBC and its methyl derivatives, 5,9-dibenzo[c,g]carbazole and N-methyl dibenzo[c,g]carbazole, on human skin HaCaT keratino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 88 publications
(135 reference statements)
0
2
0
Order By: Relevance
“…While UVA used to be considered as relatively innocuous, it now is emerging as a factor to mutagenesis 37 and damage to DNA, 38 proteins, and lipids, 39,40 thus associating it with cancer 41 and even dysregulation of immunity. 14 In ophthalmology, even though it is acceptable to use UVA for the treatment of keratoconus via collagen cross-linking, 42 studies have demonstrated that this technique becomes safer with the use of a protective ring around the limbal area to prevent damage to the stem cell compartment.…”
Section: Discussionmentioning
confidence: 99%
“…While UVA used to be considered as relatively innocuous, it now is emerging as a factor to mutagenesis 37 and damage to DNA, 38 proteins, and lipids, 39,40 thus associating it with cancer 41 and even dysregulation of immunity. 14 In ophthalmology, even though it is acceptable to use UVA for the treatment of keratoconus via collagen cross-linking, 42 studies have demonstrated that this technique becomes safer with the use of a protective ring around the limbal area to prevent damage to the stem cell compartment.…”
Section: Discussionmentioning
confidence: 99%
“…The correspondence between the time-dependent immunostaining pattern changes and the variations in gene expression levels of the markers of hemangiogenesis and lymphangiogenesis confirm that CXL treatment only temporarily suppressed these two suture-induced responses in rat corneas. UVA exposure can induce mutagenesis 27 arising from DNA and protein damage. 28 Such alterations can induce cancer 29 and even dysregulated immunity.…”
Section: Discussionmentioning
confidence: 99%